2021
DOI: 10.1186/s12992-021-00787-0
|View full text |Cite
|
Sign up to set email alerts
|

Papua New Guinea agri-food trade and household consumption trends point towards dietary change and increased overweight and obesity prevalence

Abstract: Background Papua New Guinea (PNG) experienced positive GDP growth at approximately 4.3% per year during the last decade. With increases in overall wealth within the country, PNG is facing a double burden of malnutrition: comparatively high child stunting rates and a growing overweight and obesity epidemic. We focus on the latter by evaluating trends in agri-food import data from 2001 to 2018 and household consumption data from 2018 and 2009/10. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…For example, trade policies and their impacts on processed food consumption dominated early literature on dietary transition in PICs and continues to be a key focus of research in this area. Studies found that trade liberalization, in particular, resulted not only in greater imports of ultra-processed foods but also that the ensuing competition caused a reduction in the prices of domestically-produced processed foods in low- to middle-income PICs, ultimately making processed food more affordable within Pacific communities (e.g., [ 13 , 14 , 15 , 16 ]). Nutrition reports from PICs also confirm an increase in the consumption of processed foods, including refined cereals, sugar-sweetened beverages, meat, and fats, after trade polices (including trade liberalization) came into effect in PICs (e.g., [ 12 , 14 , 15 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trade policies and their impacts on processed food consumption dominated early literature on dietary transition in PICs and continues to be a key focus of research in this area. Studies found that trade liberalization, in particular, resulted not only in greater imports of ultra-processed foods but also that the ensuing competition caused a reduction in the prices of domestically-produced processed foods in low- to middle-income PICs, ultimately making processed food more affordable within Pacific communities (e.g., [ 13 , 14 , 15 , 16 ]). Nutrition reports from PICs also confirm an increase in the consumption of processed foods, including refined cereals, sugar-sweetened beverages, meat, and fats, after trade polices (including trade liberalization) came into effect in PICs (e.g., [ 12 , 14 , 15 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that trade liberalization, in particular, resulted not only in greater imports of ultra-processed foods but also that the ensuing competition caused a reduction in the prices of domestically-produced processed foods in low- to middle-income PICs, ultimately making processed food more affordable within Pacific communities (e.g., [ 13 , 14 , 15 , 16 ]). Nutrition reports from PICs also confirm an increase in the consumption of processed foods, including refined cereals, sugar-sweetened beverages, meat, and fats, after trade polices (including trade liberalization) came into effect in PICs (e.g., [ 12 , 14 , 15 , 17 ]). Consequently, most of the recommendations on food-related interventions in PICs focus on a re-assessment of trade policies, such as increasing taxation on processed foods and limiting imports of unhealthy processed foods, including meat (e.g., [ 17 , 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The PNG populations have a history of low levels of protein consumption, which has been improving in the last years with an increase in the importation of poultry and fish (Schmidt & Fang, 2021). However, with the importation of animal-sourced foods there has also been an increased importation of ultra-processed foods, and meals containing higher saturated fat (Schmidt & Fang, 2021). PNG has poor general health due to low socio-economic status and high burden of infectious diseases, such as pneumoni a, malaria, tuberculosis and meningitis (Riley, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Papua New Guineans live in a semi‐traditional way with an agriculture‐based diet, including sago, sweet potato, taro, cassava, yam, rice, maize, breadfruit, various nuts, sugarcane, pig, chicken and fruits, like coconut, banana and pineapple (Schapper, 2017). The PNG populations have a history of low levels of protein consumption, which has been improving in the last years with an increase in the importation of poultry and fish (Schmidt & Fang, 2021). However, with the importation of animal‐sourced foods there has also been an increased importation of ultra‐processed foods, and meals containing higher saturated fat (Schmidt & Fang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas of PNG, over 90% of dietary intake is sourced through purchases from local stores and markets [2]. Nutrition transition is the concept used in the literature to describe the evolving dietary patterns within societies, marked by a shift from traditional, locally sourced diets to more processed and ultra-processed foods and beverages, which are less nutrient dense and high in deleterious nutrients, such as saturated fat, added sugar and salt [3][4][5]. The nutrition transition has also been accompanied by lifestyle changes, including less physical activity and loss of farming practices as a result of urbanisation [6].…”
Section: Introductionmentioning
confidence: 99%